Civil vengeance - King, Emily L. (Cornell University Press, 2019)
Introduction : playing the long game – Teaching revenge : social aspiration and the fragmented subject of early modern conduct books – Feeling revenge : emotional transmission and contagious vengeance in Donne's Deaths duell – Fantasizing about revenge : vagrancy and the formation of the social body in Shakespeare's 2 Henry VI and Nashe's The unfortunate traveller – Commemorating revenge : mourning, memory, and retributive alternatives in the English interregnum – Afterword : what remains of civil vengeance?.
Literaturverzeichnis: Seite 151 - 165
Keywords: English drama; English literature; Revenge in literature; Civil society in literature; Revenge